Ferric Maltol Is Effective in Correcting Iron Deficiency Anemia in Patients with Inflammatory Bowel Disease: Results from a Phase-3 Clinical Trial Program. Issue 3 (24th December 2014) - Gasche, Christoph; Ahmad, Tariq; Tulassay, Zsolt; Baumgart, Daniel C.; Bokemeyer, Bernd; Büning, Carsten; Howaldt, Stefanie; Stallmach, Andreas
Abstract : Background: Iron deficiency anemia (IDA) is frequently seen in inflammatory bowel disease. Traditionally, oral iron supplementation is linked to extensive gastrointestinal side effects and possible disease exacerbation. This multicenter phase-3 study tested the efficacy and safety of ferric maltol, a complex of ferric (Fe 3+ ) iron with maltol (3-hydroxy-2-methyl-4-pyrone), as a novel oral iron therapy for IDA. Methods: Adult patients with quiescent or mild-to-moderate ulcerative colitis or Crohn's disease, mild-to-moderate IDA (9.5–12.0 g/dL and 9.5–13.0 g/dL in females and males, respectively), and documented failure on previous oral ferrous products received oral ferric maltol capsules (30 mg twice a day) or identical placebo for 12 weeks according to a randomized, double-blind, placebo-controlled study design. The primary efficacy endpoint was change in hemoglobin (Hb) from baseline to week 12. Safety and tolerability were assessed. Results: Of 329 patients screened, 128 received randomized therapy (64 ferric maltol-treated and 64 placebo-treated patients) and comprised the intent-to-treat efficacy analysis: 55 ferric maltol patients (86%) and 53 placebo patients (83%) completed the trial. Significant improvements in Hb were observed with ferric maltol versus placebo at weeks 4, 8, and 12: mean (SE) 1.04 (0.11) g/dL, 1.76 (0.15) g/dL, and 2.25 (0.19) g/dL, respectively ( P < 0.0001 at all time-points; analysis of covariance). Hb was normalized in two-thirds of patients by week 12. The safety profile of ferric maltol was comparable with placebo, with no impact on inflammatory bowel disease severity. Conclusions: Ferric maltol provided rapid clinically meaningful improvements in Hb and showed a favorable safety profile, suggesting its possible use as an alternative to intravenous iron in IDA inflammatory bowel disease.